Domoljubje v slovenskem šolskem sistemu - Prebilič, Vladimir (Šolsko polje, 2011)
In Slovenia, discussions of patriotism face strong challenges. In view of the various standpoints, they may be organized into two reciprocally different and conceptually distant groups. The first rather liberal group consists of individuals that deem an emphasis on the concept of patriotism unnecessary because a new, substantially broader European framework is supposed to progressively replace it. In this respect, fostering patriotic sentiments may be seen as inhibiting (at least in part) the further strengthening of European identity, for which new associations among world economic and military superpowers will most likely be instituted at the global level. The second less liberal and perhaps somewhat more conservative position on patriotism signifies an antipode to the premises above. Furthermore, the question arises: What is or will the role of government, public authorities, and systems be in the development and implementation of patriotism as a concept, and how will these contribute to resolving many open issues that pertain to patriotism in Slovenia? This article highlights the understanding of aspects related to the origin of an independent and self-governing Slovenia that may be considered significant patriotic ideas.
Keywords: izobraževalni sistemi; patriotism; European Union; domoljubje; domovinska vzgoja; education policies; nacionalna identiteta; national identity; osamosvojitev; history; European identity; patriotizem; Slovenian education system; zgodovina; Slovenia; evropska identiteta; Slovenija; world economic superpowers; world military superpowers; raziskave